A colheita da floresta: Uma estratégia de desenvolvimento social e economicamente viável ao desmatamento? - Patricia Andrade de Oliveira (Confins)
The World Conference of Environment and Development (WCED), held in Rio d Janeiro in June of 1992, was a unique international relations event in the and definitely gave the environment its deserved position in the international agenda as a global concern.During the so-called Rio 92, governmental strategies for the development of local social and economically sustainable development were suggested. Also, the Biodiversity Convention, which took place during the WCED, highlighted the sovereignty of nations over their biological resources and defined that each country should create its own conditions to facilitate access to genetic resources while promoting the fair and equitable sharing of the benefits derived from the use of such resources.Central to this process are debates over the role of the economic activity in environmental protection, especially the protection of the world’s biodiversity resources upon which the whole economic and climatic systems depend.This paper examines the theory behind some modern development strategies, such as the one that supports that the market economy will save the world’s biodiversity. According to this line of thought, the conservation of biodiversity resources must go hand in hand with its potential to generate income, in other words, economic incentives would ultimately encourage local communities to efficiently protect their forests.The Rainforest Harvest is an example of market-oriented strategy aimed at conciliating both the objectives of conservation and use of biodiversity resources. It is based on the sustainable extraction of non-timber-forest products (NTFPs) so as not to interfere with the balance of both the ecosystems and the food-chain. The principle of the Rainforest Harvest is, therefore, that if it can be shown that forests are more valuable while they are standing, they will have more chance to be preserved.This article examines the partnership deal between the British cosmetics company The Body Shop and the Kaiapó communities Pycany and A’Ukre in the the brasilian state of Pará. It is divided into five parts. The first part examines deforestation as a consequence of governmental development projects in the Amazon during the 1970’s. Such projects had impacts on the local population, especially on indigenous communities and made their access to land even more difficult. The second part deals with the notions behind most market-based development strategies, like the “Ecodevelopment” and “Sustainable Development” while the third part presents the Kaiapós involved in Rainforest Harvest trade-agreement. The fourth part examines the controversies over the “harvest” concept as a socially and economically equitable alternative to deforestation. The fifth part presents the case-study of the trade partnership between the company The Body Shop and the Kaiapó community for the supply of Brazil nut oil.